A worksheet, a whiteboard, a teacher-learner: leveraging materials and colonial language frames for multimodal indigenous language learning. Issue 1 (3rd April 2021) - Engman, Mel M.
ABSTRACT: The growing demand for Indigenous language education in the United States often relies on community teachers with widely varying proficiencies as part of local language reclamation efforts. While these English-dominant 'teacher-learners' play a central role in the success of classroom-based K-12 language programs, their classroom experiences and practices have received little attention in second language acquisition research. I address this gap in the literature by examining an English-dominant Ojibwe teacher-learner's pedagogical practices in an English-dominant tribal school. I theorise the use of colonial language and materials by relying on linguistic ethnography's multi-scalar approach to language in use as well as a focus on sign-makers' transformations of local resources. Findings show how the teacher-learner's reliance on relational knowledge and colonial language framing scaffolds translingual practices and opens up discursive space for learners to experiment, play, and learn. This study highlights how one teacher-learner negotiates the ideological and material conditions that shape the learning and use of an Indigenous language within a colonial institution (school) that has long been a tool of assimilation and erasure.